An unusual psychiatric presentation of polycythaemia 'Difficulties lie in our habits of thought rather than in the nature of things' Andre Tardieu. (9th April 2013) - Rai, Rahul; Pieters, Thirza
Abstract : Psychiatric symptoms are not always best explained in the context of psychological stress. The same mental, emotional and behavioural changes also arise from various medical conditions. For a clinician this dual origin of psychiatric symptoms creates an ongoing diagnostic challenge. Our patient is a 50-year-old gentleman who had been working in a company for around 33 years and always had good appraisals. He presented to mental health services with a 5-year history of persecutory beliefs, convinced that his employers were out to damage his reputation. Apart from a diagnosis of polycythaemia, a few months before the onset of abnormal beliefs, there is no personal or family history of psychiatric disorder or medical illness. His delusions did not respond to conventional treatment with psychotropic medication possibly due to non-adherence because of side effects. However, a series of venesections lead to an improvement in mental state.